The Performance and Soft Skills: Islamic Higher Education Institutions in Indonesia - Vegalyra Novantini Samodra (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The challenge of Higher Education Institutions (HEIs) in Indonesia plays a crucial role and requires enhancement. The pivotal role of HEIs in Indonesia is multifaceted. These institutions play a crucial part in shaping the country's cultural and religious identity, while also providing education that aligns with contemporary demands. This study explored the performance and soft skills among lecturers and administration staff in Islamic HEIs. The study emphasizes performance and soft skills based on managerial effectiveness in Islamic HEIs in Indonesia. The performance and soft skills explored from critical analyses of global literature. The study was conducted in Lombok, Indonesia, among 3 Islamic HEIs. Methods used were literature review, observation, and in-depth interviews. The software used was NVIVO 14 with the relative thematic analysis of the study. Findings on the HEIs model soft skills proposed to address enhancing administration staff performance and lecturer performance. By nurturing these soft skills, organizations thrive when they cultivate alignment, creativity, adaptability, and effective management and avoid mushroom management. Mushroom management in the context of organizational management and leadership styles represents a management style that is characterized by secrecy, lack of transparency, and limited employee involvement in decision-making processes. The results proposed the model to address enhancing administration staff performance through alignment value, change management, and Islamic leadership. The model addresses enhancing lecturer performance through alignment value, change management, Islamic leadership, and divergent thinking. By nurturing these soft skills, organizations thrive when they cultivate alignment, creativity, adaptability, and effective performance management. Administration staff performance impacts the lecturer’s performance besides the lecturer’s performance itself. Research suggests that organizations can benefit greatly from nurturing soft skills and adopting more transparent and inclusive leadership practices to avoid mushroom management. The practical implication of this research proposed model for enhancing administration staff and lecturer performance in Islamic higher education institutions (HEIs) includes administration staff performance enhancement through aligning individual roles with organizational objectives, implementing change management strategies, monitoring performance through key indicators, and applying Islamic leadership principles. Lecturer Performance enhancement through aligning course objectives with institutional goals encouraging research alignment, promoting pedagogical innovations, and fostering visionary leadership.